IMPLEMENTATION OF COMPETENCY-BASED ASSESSMENT MODEL IN OPERATIONAL PRACTICAL TEST - Irwan Irwan; Riki Wanda Putra; Sarifuddin Sarifuddin; Budi Riyanto; Melda Yanti; M. Kurniawan; Hasri Devin; Sidrotul Muntaha; Heri Sutanto; Erita Erita; Mauli Denil; Daffa Ulhaq; Balqis Nurhamida (As-Sidanah, 2025)
The absence of a standardized operational-level practical test instrument for Technology Nautical Study Program cadets has led to inconsistencies in evaluating critical competencies, ultimately affecting the quality of training and readiness in maritime operations. This community service activity was initiated to address this gap by identifying the root causes behind the lack of implementation, such as inadequate alignment between practical assessments and core competencies, and by highlighting the consequential impact on vocational education quality. Using a qualitative approach through lectures, training sessions, and Participatory Action Research (PAR), this study involved lecturers and cadets from AMSS and Poltekpel Barombong. The intervention focused on socializing and implementing a competency-based assessment instrument that, based on preliminary indicators and observational data, demonstrated improvements in measuring participant skills with increased objectivity, validity, and reliability. However, limitations remain in that the instrument currently addresses only operational-level competencies and does not fully encompass all practical scenarios aligned with core competencies. The findings underscore the need for further research to expand and refine assessment tools, particularly at the management level, thereby contributing to enhanced vocational training and competency-based education in the nautical field.